The Effects of QR Code-Supported Training on Cast-Related Problems at Home and Quality of Life in Patients with a Cast: A Pilot Randomized Controlled Study. - ÖZBAŞ, Nilgün; KORKMAZ, Murat (Turkiye Klinikleri Journal of Nursing Sciences, 2024)
Objective: Many individuals who have cast after fractures experience cast-related problems due to a lack of knowledge. The lack of knowledge about cast care leads to difficulties in properly managing the cast, resulting in various problems during the healing process. The aim of this randomized controlled study is to examine the effect of a QR code-supported training on cast-related problems at home and quality of life in patients with a cast. Material and Methods: A total of 40 participants were randomly assigned to the intervention (n=20) and control (n=20) groups. The intervention group was given QR code-supported patient training. Data were collected with "Patient Information Form", "Form for Problems Experienced with the Cast at Home" and "SF-36 Quality of Life Scale". In the evaluation of the data, descriptive statistics (mean, standard deviation, frequency, and percentage), Mann-Whitney U test, Spearman correlation coefficient, chi-square test, Mixed Design ANOVA test, and Bonferroni-Dunn test were used. Study findings were reported based on the CONSORT Statement. Results: After QR code-supported training, the intervention group experienced significantly reduced problems and higher quality of life scores (p<0.05). The rate of admission to the emergency department was lower in the intervention group (p=0.011). It was determined that the problems experienced with the cast were negatively correlated with the quality-of-life scores (p<0.05). Conclusion: QR code-supported training reduced the problems associated with the cast at home and positively impacted the quality of life. Additionally, QR-supported training was identified as a nursing intervention that reduces hospital readmissions.